(untitled) - Lymbery, Sylvia (London, 2007)
Colloquial Italian is designed to help those involved in self-study; structured to give you the opportunity to listen to and read lots of modern, everyday Italian, it has also been developed to work systematically on reinforcing and extending your grasp of Italian grammar and vocabulary. Key features of Colloquial Italian 2 include: · Revision material to help consolidate and build up your basics · A wided range of contemporary authentic documents, both written and audio · Lots of spoken and written exercises in each unit · Highlighted key structures and phrases, a Grammar reference and detailed answer keys · A broad range of situations, focusing on day to day life in Italy · Supplementary exercises and Italian language web-links at www.colloquials.routledge.com Audio material is available on two 60-minutes cassettes and CDs to accompany Colloquial Italian. Recorded by native speakers, this material will help you perfect your pronunciation andlistening skills.
Keywords: Italian language,Italian language,Italian language-Spoken Italian,Ngôn ngữ Ý; Conversation and phrase books-English,Textbooks for foreign speakers-English